Decentralized Water Systems for Sustainable and Reliable Supply. (2015) - Piratla, Kalyan R.; Goverdhanam, Suraj
Abstract: The water utility industry is under enormous pressure to meet the challenges of increasing demands due to population growth and lifestyle changes, and depleting freshwater resources. Deteriorating supply infrastructure makes the task of meeting water demands even more challenging. The combination of source and supply challenges encouraged the consideration of sustainable and reliable alternatives for future water supply management. On-site greywater reuse is one such alternative that is becoming increasingly popular for its sustainable benefits such as ready availability, energy savings, reduced freshwater withdrawals and less effluent runoff. While the treatment technologies for making it economically viable are currently being investigated by other researchers, this paper investigates the improvement in supply reliability when traditional water supply systems are complemented by on-site greywater reuse. A robust computational model is developed for quantifying reliabilities of traditional and on-site greywater reuse systems for a given study area. The results revealed that there is up to 17% of improvement in supply reliability due to the on-site greywater reuse systems. A one-way sensitivity analysis conducted on the results indicated that the observed reliability improvement is sensitive to system age, pipeline roughness, treatment efficiency and allowable use of reclaimed water. Further research is needed to investigate the value of this reliability improvement by considering the life cycle cost and energy implications of on-site greywater reuse alternative.